The human factor and the University: the case of University of Zimbabwe - Muzvidziwa, Victor N. (2016)
Culture, and the Human Factor (HF') dimension have largely been ignored in studies of Universities. Most studies on universities have focused on administrative, managerial, operational and academic programmes as well as policy aspects at the expense of the human side (Harman. 1989). According to Harman (1989) the university has been conceptualised as a bureaucracy, as a loosely coupled system. as an organised anarchy. as a normative and professional organisation. but not as a human and symbolic entity consisting of a network of networks of individuals. It is true that both the 1989 and 1998 Commissions of inquiry following disturbances on UZ campus as well as the 1998 Canadian Change Agency consultants did not bring to the fore the centrality of the HF' in their recommendations and the way forward for UZ. The main focus of Commission reports has been on good governance. If anything it is partly the neglect of the HF that explains the absence of meaningful dialogue and a positive academic culture on UZ Campus in pursuit of the institution's mission.